THE ANALYSIS OF WAYS TO IMPROVE ECONOMIC DEVELOPMENT AND TRADE ORGANIZATION OF TRANSPORTATION ON AIR TRANSPORT - I. A. Ivanov (Научный вестник МГТУ ГА, 2016)
In transport system of Russia air transport is one of main types of passenger and cargo transport. Demand for air transportation constantly increases that allows to consider reasonably improvement of transportations on air transport as the priority direction of development in civil aviation. The article considers issues of development of the branch air transport.